The round-robin approach applied to nanoinformatics: consensus prediction of nanomaterials zeta potential - Varsou, Dimitra-Danai; Banerjee, Arkaprava; Roy, Joyita; Roy, Kunal; Savvas, Giannis; Sarimveis, Haralambos; Wyrzykowska, Ewelina; Balicki, Mateusz; Puzyn, Tomasz; Melagraki, Georgia; Lynch, Iseult; Afantitis, Antreas (Beilstein Journal of Nanotechnology, 2024)
A key step in building regulatory acceptance of alternative or non-animal test methods has long been the use of interlaboratory comparisons or round-robins (RRs), in which a common test material and standard operating procedure is provided to all participants, who measure the specific endpoint and return their data for statistical comparison to demonstrate the reproducibility of the method. While there is currently no standard approach for the comparison of modelling approaches, consensus modelling is emerging as a “modelling equivalent” of a RR. We demonstrate here a novel approach to evaluate the performance of different models for the same endpoint (nanomaterials’ zeta potential) trained using a common dataset, through generation of a consensus model, leading to increased confidence in the model predictions and underlying models. Using a publicly available dataset, four research groups (NovaMechanics Ltd. (NovaM)-Cyprus, National Technical University of Athens (NTUA)-Greece, QSAR Lab Ltd.-Poland, and DTC Lab-India) built five distinct machine learning (ML) models for the in silico prediction of the zeta potential of metal and metal oxide-nanomaterials (NMs) in aqueous media. The individual models were integrated into a consensus modelling scheme, enhancing their predictive accuracy and reducing their biases. The consensus models outperform the individual models, resulting in more reliable predictions. We propose this approach as a valuable method for increasing the validity of nanoinformatics models and driving regulatory acceptance of in silico new approach methodologies for the use within an “Integrated Approach to Testing and Assessment” (IATA) for risk assessment of NMs.
Keywords: consensus modelling; read-across; QSPR; round-robin test; zeta potential